Microstructure Evolution and Surface Quality of Laser-Sintered Maraging Steel Parts Produced on Different Building Platform Positions - Öter, Zafer Çağatay; Gencer, Yücel; Tarakçı, Mehmet (Elsevier, 2020)
This study reveals the effects of building platform position on the surface quality and microstructure of maraging steel parts fabricated by Direct Metal Laser Sintering (DMLS). Six identical parts were produced with the same parameters in the corners and at the center of the EOS M290 building platform. Surface roughness of vertical, horizontal and inclined surfaces were evaluated. Dimensional and geometric accuracy was investigated by comparing the actual dimensions of the parts with the dimensions of the solid design as well as imaging geometrical details. Microstructure of the parts were investigated using optical microscope and scanning electron microscope. Results showed that the surface quality and melt pool profile varies depending on the positions of the parts on the building platform.
Keywords: Laser Sintering; Additive Manufacturing; Surface Quality; Maraging Steel; DMLS